Spatial variation of plastic pellet abundance on Santos beach, São Paulo, Brazil (Research, Society and Development, 2022)
The study aims to determine the current spatial distribution of plastic pellets on Santos beach, both along the longitudinal axis of the beach and along the tidal lines, and to assess the amount of entry of this material. To determine the spatial distribution of plastic pellets, 108 sample elements were collected with a square area of ​​1.0 m on side removed from the sediment with a depth of 10 cm, totaling 0.1 m3. Sampling took place in the summer of 2020, from 01/08 to 03/21. 11,979 pellets were collected.  Relatively to the sample beach areas, the wrack line zone presented the highest numerical densities in sections 9 and 8, with averages of 742.000±237.765 pellets/0.1 m³ and 617.333±77,242 pellets/0.1 m³, respectively. Regarding the longitudinal axis of the beach, pellets were found in abundance in section 5, located in the central region of the beach, which is influenced by hydrodynamics and marine currents, where the highest numerical density was observed in the dry zone with an average of 188.667±127.563 pellets/0.1 m³ and an average of 584.000±343.167 pellets/0.1 m³ in wrack line zone. When analyzing the numerical density of pellets inlet, section 9 had highest average in wrack line zone, which receives the deposit of material brought by marine currents, near the entrance to the Port of Santos where takes place the active transport of these microplastics. The results indicate that the pellet depositional zone occurs between channels 3 and 4 and at Ponta da Praia.